Legitimacy and activities of civil society organizations - Peter Kotzian; Jens Steffek (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2011)
Civil Society Organizations (CSOs) play an active and noteworthy role in governance, both at the national and international level. Three questions arise: First, how do CSOs exercise their advocacy, what repertoires, strategies and resources do they use? Second, to what degree are they legitimized to do so? Third, are there systematic differences between member and non-member CSOs, respectively between policy fields? Based on a survey of 60 exemplary CSOs covering four distinct international-level policy making fora, we will inquire into these questions. The central finding is that membership CSOs neither differ substantially from non-member CSOs in their roles and strategies of dealing with International Organizations, nor do they differ in other aspects of legitimacy, such as transparency or inclusion of beneficiaries. There are no systematic patterns in CSOs properties or behavior which correspond to policy fields. – – Zivilgesellschaftliche Organisationen (ZGO) spielen im modernen Regieren eine wichtige Rolle, sowohl im Staat als auch auf internationaler Ebene. Drei Forschungsfragen stehen im Mittelpunkt dieses Papiers: Erstens, wie genau nehmen ZGO am Regierungsprozess teil und welche Einflussstrategien, Ressourcen und Handlungsrepertoire nutzen sie dabei? Zweitens, wie steht es um die Legitimation dieser Organisationen und ihrer Aktivitäten? Drittens, verhalten sich ZGO mit zahlreichen Mitgliedern systematisch anders als ZGO ohne Mitgliedschaft? Gestützt auf Daten von 60 transnationalen ZGO aus vier verschiedenen Politikfeldern gehen wir diesen Fragen nach. Zentrales Ergebnis ist, dass ZGO mit breiter Mitgliedschaft sich in ihren Rollenverständnis und ihren Einflussstrategien nicht grundlegend von anderen unterscheiden. Auch im Hinblick auf wichtige Aspekte ihrer Legitimität, wie etwa Transparenz oder Einbindung von Regelungsadressaten, gibt es keine auffälligen Unterschiede. Die Politikfelder, in denen ZGO aktiv sind, haben ebenfalls keinen messbaren Einfluss auf ihr Handlungsrepertoire und ihre politischen Strategien.
Keywords: 300